What’s so Funny? Democritus ridens in Juvenal 10 - Adomėnas, Mantas (Literatūra, 2022)
The article analyzes Juvenal’s use of Democritean material in his tenth Satire. The famous juxtaposition of laughing Democritus and weeping Heraclitus (which popularized and perpetuated the image of contrasting philosophers) is habitually interpreted in terms of Juvenal’s poetic strategy, as indicating the shift in the tone of his satires and the change of Juvenal’s stance from the anger as the dominant emotion of his earlier satires to laughter and irony of the later ones. There is a tendency to assume that the totality of Democritean material in Juvenal 10 derives solely from Seneca. However, close reading of the concluding lines of the Satire suggests a different argumentative strategy and deeper engagement with Democritus’ thought by Juvenal. The comparison with Pseudo-Hippocratic ‘epistolary novel’ suggests Cynic diatribai as the source of the Democritean material in Juvenal 10.
Keywords: Democritus; Juvenal; Heraclitus; Satire; Cynicism; Ancient Philosophy